Commuter Line (KRL) Passenger Perception Against Government Policies Of The Covid 19 Pandemic Era At Jakarta Kota Station - Dhina Setyo Oktaria; Sapto Priyanto; Arief Darmawan (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2022)
The Indonesian government issued policies to deal with the COVID-19 pandemic, one of which was urban rail transportation such as the Jabodetabek KRL. This KRL carried many passengers every day. This research aimed to provide input for the government as a regulator related to policies in the rail transportation and for operators as implementers of services at stations and train travel. The research was conducted at the Jakarta city station with 99 respondents. The results revealed that 60% of respondents wanted a cross sign on the station waiting room bench to sit, 71% of respondents washed their hands when getting off the train, and 48% of respondents washed their hands or used hand sanitizer after tapping in on the ticket machine. During the trip, 70% of respondents used hand sanitizers and 62% of respondents obeyed the rules not to speak one way or two ways by telephone or in person. In open-ended questions, 38.61% of respondents wanted all passengers and operators to comply with and tighten health protocols, 12.87% of respondents wanted operators to provide the best service for passengers, and 8.91% of respondents wanted operators to notice the number of passengers during rush hour. The researcher also found that there were no more restrictions and partitions for the seats because there were many passengers standing. Researchers expected that the Covid-19 pandemic will end soon.